MnZn-BASED FERRITE AND METHOD FOR PRODUCING MnZn-BASED FERRITE

A tailored MnZn-based ferrite composition and manufacturing process enhance magnetic flux density and reduce core loss, addressing the need for improved performance in high-temperature environments.

JP2025010786APending Publication Date: 2025-01-23TOKIN CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023112999
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

MnZn-based ferrites used in high-temperature environments require improved maximum magnetic flux density characteristics to enhance DC superimposition in high-frequency applications.

Method used

A specific composition of MnZn-based ferrite comprising Fe2O3, ZnO, and MnO, with additional components like SiO2, CaO, and Co2O3, and a manufacturing process involving sintering, crushing, and heat-treating to achieve a particle size of 1.2 μm or less, ensuring high magnetic flux density and low core loss.

Benefits of technology

The resulting MnZn-based ferrite exhibits maximum magnetic flux density of 450 mT at 100°C and low unit volume core loss, suitable for high-temperature and high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010786000001
    Figure 2025010786000001
Patent Text Reader

Abstract

To provide an MnZn-based ferrite having good characteristics of a maximum magnetic flux density Bm even in a high temperature environment.SOLUTION: An MnZn-based ferrite according to an aspect of the present invention contains Fe2O3, ZnO and MnO as a main component, wherein Fe2O3 is 56.0 to 59.0 mol%, ZnO is 2.5 to 7.0 mol% and the balance is MnO in 100 mol% of the main component. The MnZn ferrite further contains, in relation to 100 mass% of the main component, 0.010-0.050 mass% of SiO2, 0.020-0.060 mass% of CaO, and 0.150-0.350 mass% of Co2O3, as a sub-component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a MnZn-based ferrite and a method for producing the MnZn-based ferrite. [Background technology]

[0002] MnZn ferrite has properties such as high magnetic permeability, high magnetic flux density, and ease of magnetization even in small magnetic fields, and is widely used in communication equipment, power supplies, etc. Various studies have been conducted on MnZn ferrite to obtain properties suited to the application.

[0003] Patent Document 1 describes a MnZn-based ferrite sintered body that has low core loss over a wide temperature range at high frequencies of 300 to 500 kHz and that exhibits small changes in core loss over time in high-temperature environments, and contains a specific amount of Fe 2 O 3 The main components are ZnO and MnO, and a specific amount of SiO 2 , CaCO 3 , Co 3 O 4 , ZrO 2 , and Ta 2 O 5 The average crystal grain size is 3 μm or more and less than 8 μm, and the sintered body density is 4.65 g / cm 3 The above MnZn-based ferrite sintered bodies are disclosed.

[0004] Patent Document 2 discloses a low-loss MnZn-based ferrite that contains Fe, Mn, and Zn as main components, Co, Ca, and Si as a first minor component, and a specific amount of a Va group element as a second minor component, and has an average crystal grain size of less than 3.2 μm and a volume resistivity of 1 Ω m or more, as an MnZn-based ferrite that has low power loss over a wide temperature range and operating magnetic flux density even at high frequencies of 1 MHz or more. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 181242 [Patent Document 2] International Publication No. 2006 / 054749 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, MnZn ferrites are used in various environments, for example, in high-temperature environments. In addition, in order to improve the DC bias characteristics of products using high-frequency low-loss ferrites, ferrites with good maximum magnetic flux density Bm are required. For this reason, ferrites with good maximum magnetic flux density Bm characteristics are required even in high-temperature environments.

[0007] In view of the above problems, an object of the present invention is to provide an MnZn-based ferrite having good maximum magnetic flux density Bm characteristics even in a high-temperature environment, and a method for producing the MnZn-based ferrite. [Means for solving the problem]

[0008] The MnZn ferrite according to one embodiment of the present invention is 2 O 3 The main components are ZnO and MnO, and in 100 mol% of the main components, Fe 2 O 3 The main component is 100 mass %. 2 0.010 to 0.050 mass%, CaO 0.020 to 0.060 mass%, Co 2 O 3 The content is 0.150 to 0.350 mass %.

[0009] The above-mentioned MnZn ferrite may further contain 0.010 to 0.100 mass % of ZrO as a secondary component.

[0010] The above-mentioned MnZn ferrite may have a maximum magnetic flux density Bm at 100° C. of 450 mT or more.

[0011] The above-mentioned MnZn ferrite has a sintered density of 4.9 g / cm 3 It may be more than that.

[0012] The above-mentioned MnZn ferrite has a core loss per unit volume (Pcv) of 250mW / cm at 100℃, 1MHz, and 50mT. 3 It may be the following.

[0013] The above-mentioned MnZn ferrite may have a magnetic permeability μ at 25° C. of 450 or more.

[0014] A method for producing MnZn-based ferrite according to one aspect of the present invention is a method for producing the above-mentioned MnZn-based ferrite, in which, after sintering, Fe in 100 mol % of the main component is 2 O 3 a step of mixing raw materials containing each main component so that the composition is 56.0 to 59.0 mol %, 2.5 to 7.0 mol % of ZnO, and the remainder is MnO; and 2 0.010-0.050 mass%, CaO 0.020-0.060 mass%, Co 2 O 3 and pulverizing the resulting mixed powder until it becomes a pulverized powder having a D90 particle size of 1.2 μm or less.

[0015] The above-mentioned method for producing MnZn-based ferrite may further include a step of molding the crushed powder and heat treating it at 1150 to 1250°C. Effect of the Invention

[0016] According to the present invention, it is possible to provide an MnZn-based ferrite having good maximum magnetic flux density Bm characteristics even in a high-temperature environment, and a method for producing the MnZn-based ferrite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The MnZn-based ferrite and the method for producing the MnZn-based ferrite according to the present invention will be described below. Note that unless otherwise specified, the symbol "to" indicating a numerical range includes the lower limit and the upper limit.

[0018] [MnZn ferrite] The MnZn-based ferrite according to the present invention (hereinafter also referred to as the present MnZn-based ferrite) has the following features: Fe 2 O 3 It contains ZnO and MnO as its main components. In 100mol% of the main components, Fe 2 O 3 is 56.0 to 59.0 mol %, ZnO is 2.5 to 7.0 mol %, and the remainder is MnO, As a subcomponent, SiO 2 0.010 to 0.050 mass%, CaO 0.020 to 0.060 mass%, Co 2 O 3 The content is 0.150 to 0.350 mass %.

[0019] This MnZn ferrite is Fe 2 O 3 The main components of this MnZn ferrite are Fe, ZnO, and MnO. 2 O 3 is 56.0 to 59.0 mol%, ZnO is 2.5 to 7.0 mol%, and the remainder (34.0 to 41.5 mol%) is MnO.

[0020] Fe 2 O 3 By making the content of Fe 56.0 mol % or more, preferably 57.0 mol % or more, MnZn ferrite with a high maximum magnetic flux density Bm at 100° C. can be obtained. 2 O 3 By making it 59.0 mol % or less, preferably 58.0 mol % or less, a MnZn ferrite having a low unit core loss (Pcv) at 100° C., 1 MHz and 50 mT and a high magnetic permeability μ at 25° C. can be obtained.

[0021] Furthermore, by making the ZnO content 2.5 mol % or more, preferably 3.5 mol % or more, a MnZn-based ferrite with low core loss per unit volume (Pcv) at 100°C, 1 MHz, and 50 mT can be obtained. On the other hand, by making the ZnO content 7.0 mol % or less, preferably 5.5 mol % or less, a MnZn-based ferrite with high maximum magnetic flux density Bm at 100°C can be obtained.

[0022] In addition, this MnZn ferrite contains at least SiO as a secondary component. 2 , CaO, and Co 2 O 3 Contains:

[0023] SiO 2 By setting the content to 0.010 mass % or more, preferably 0.015 mass % or more, more preferably 0.025 mass % or more, and 0.050 mass % or less, preferably 0.045 mass % or less, it is possible to obtain a MnZn-based ferrite having a low unit core loss (Pcv) at 100°C, 1 MHz, and 50 mT.

[0024] Furthermore, by setting the CaO content to 0.020 mass% or more, preferably 0.025 mass% or more, more preferably 0.030 mass% or more, and 0.060 mass% or less, preferably 0.055 mass% or less, more preferably 0.045 mass% or less, it is possible to obtain a MnZn-based ferrite having a low unit core loss (Pcv) at 100°C, 1 MHz, and 50 mT.

[0025] In addition, Co 2 O 3 By making the content of Co 0.150 mol % or more, preferably 0.250 mol % or more, a MnZn ferrite having a low core loss per unit volume (Pcv) at 100° C., 1 MHz, and 50 mT can be obtained. 2 O 3 By making the content of MnZn ferrite 0.350 mol % or less, and preferably 0.300 mol % or less, it is possible to obtain a MnZn ferrite having a high magnetic permeability μ at 25° C.

[0026] The MnZn-based ferrite may further contain other components within the range in which the effects of the present invention are exhibited. Examples of other components include other metal oxides that are added as necessary and elements that are inevitably contained. Examples of other metal oxides include ZrO 2 , Ta 2 O 5 , Nb 2 O 5 , Bi 2 O 3 , MoO 3 Among them, ZrO 2 In addition, examples of elements that are inevitably contained include C (carbon atom), P (phosphorus atom), and B (boron atom).

[0027] This MnZn ferrite is ZrO 2 By setting the content to 0.010 mass % or more, preferably 0.030 mass % or more, and 0.100 mass % or less, preferably 0.060 mass % or less, more preferably 0.050 mass % or less, it is possible to obtain a MnZn-based ferrite having a low unit core loss (Pcv) at 100°C, 1 MHz, and 50 mT.

[0028] ZrO 2 The total content of other metal oxides and elements excluding the above is preferably 0.1 mass % or less, and more preferably 0.01 mass % or less, based on 100 mass % of the main component.

[0029] In the MnZn ferrite described above, Fe 2 O 3 Since the content of Mn is increased and the content of ZnO is decreased, the Curie temperature Tc can be increased, and the maximum magnetic flux density Bm at 100°C can be increased to 450 mT or more. Therefore, it is possible to provide a MnZn-based ferrite having good maximum magnetic flux density Bm characteristics even in a high temperature environment.

[0030] In addition, since the MnZn ferrite has the above composition, the core loss per unit volume (Pcv) at 100°C, 1MHz, and 50mT is 250mW / cm 3The following MnZn-based ferrite is obtained: In addition, since the present MnZn-based ferrite has the above composition, the MnZn-based ferrite has a magnetic permeability μ of 450 or more at 25° C. is obtained.

[0031] The present MnZn-based ferrite can be particularly suitably used in power supply circuits used in high frequency and high temperature environments, such as in servers.

[0032] [Manufacturing method of MnZn ferrite] Next, one embodiment of a method for producing MnZn ferrite (hereinafter also referred to as the present production method) will be described.

[0033] The present manufacturing method is a method capable of suitably manufacturing the present MnZn-based ferrite, and at least after sintering, Fe in 100 mol% of the main component is 2 O 3 a step of mixing raw materials containing each main component so that the composition is 56.0 to 59.0 mol %, ZnO is 2.5 to 7.0 mol %, and the remainder is MnO (mixing step); 2 0.010-0.050 mass%, CaO 0.020-0.060 mass%, Co 2 O 3 The present manufacturing method may include a step of adding raw materials containing each of the minor components so that the powder contains 0.150 to 0.350 mass % of each of the minor components (adding step), and a step of crushing the obtained mixed powder until the powder becomes a crushed powder having a D90 particle size of 1.2 μm or less (crushing step). The present manufacturing method may further include a drying / granulation step of adding a binder to the mixed powder of the major components after the mixing step to form granules, a calcination step of calcining the obtained granules, a drying / granulation step for the crushed powder, a molding step of molding the crushed powder or its granules, and a heat treatment step (sintering step) of heat treating the molded body.

[0034] In the mixing step, the main components are mixed so that the main components after sintering have the composition of the present MnZn ferrite. The form of the main components before mixing is not particularly limited, but it is preferable that they are in a powder form from the viewpoint of easy handling and uniform mixing. The raw material powders of the main components are mixed and crushed as necessary to obtain a mixed powder. The mixing and crushing method may be appropriately selected from known methods. Specific examples include an attritor and a bead mill. The particle size of the mixed powder is not particularly limited, but it is preferable to adjust the median diameter D50 to 0.5 μm to 1.5 μm from the viewpoint of uniformity. The particle size D50 and D90 described later are the particle size (D50) and particle size (D90) at which the cumulative frequency of the particle size is 50% and 90%, respectively, when the particle size distribution of the target particles is measured. The particle size distribution of the mixed powder can be measured with a particle size distribution measuring device.

[0035] The mixed powder of the main components may be subjected to a drying and granulation process. In the drying and granulation process, for example, 0.5 to 1 part by mass of a binder such as polyvinyl alcohol is added to the mixed powder obtained in the mixing process when the total mass of the mixed powder is 100 parts by mass, and granules can be obtained by spraying using a spray dryer or the like. The obtained granules may then be calcined, for example, at 750°C in an air atmosphere for about 1 hour to obtain a calcined product (calcination process).

[0036] Next, the auxiliary components are added to the calcined product so that the auxiliary components after sintering have the composition of the present MnZn ferrite. The form of the auxiliary components before addition is not particularly limited, but it is preferable that the auxiliary components are in a particulate form from the viewpoint of easy handling and uniform mixing.

[0037] After adding the subcomponents, the resulting mixed powder is crushed to obtain crushed powder. Crushing may be appropriately adjusted so that the average crystal grain size of the resulting MnZn-based ferrite is 6 μm or less. For example, the calcined product is crushed until the D90 of the grain size after crushing is 1.2 μm or less.

[0038] In the drying and granulation process, 0.5 to 1.0 parts by mass of a binder such as polyvinyl alcohol is added to the crushed powder obtained in the crushing process when the total mass of the crushed powder is 100 parts by mass, and granules are obtained by spraying with a spray dryer, etc. At this time, it is desirable that the median diameter D50 of the granules is 40 μm or more and 200 μm or less.

[0039] In the molding process, the granules obtained in the drying and granulation process are molded into a predetermined shape. The predetermined shape may be designed according to the application, etc. For example, the granules are molded into a toroidal core with an outer diameter of 15 mm, an inner diameter of 10 mm, and a height of 6 mm.

[0040] The molded granules are heat-treated to form a sintered body (MnZn ferrite). The heat treatment (sintering) conditions are preferably 1150 to 1250°C for several hours. By performing heat treatment at 1150°C or higher, the sintered density can be increased to 4.9 g / cm. 3 Furthermore, MnZn ferrite with a high maximum magnetic flux density Bm at 100°C can be obtained. On the other hand, by performing heat treatment at 1250°C or less, MnZn ferrite with low core loss per unit volume (Pcv) at 100°C, 1 MHz, and 50 mT can be obtained.

[0041] According to the present invention described above, it is possible to provide a MnZn-based ferrite having good maximum magnetic flux density Bm characteristics and low loss even in a high temperature environment, and a method for producing the MnZn-based ferrite. EXAMPLES

[0042] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these descriptions.

[0043] [Example 1] Sintered Fe 2 O 3The raw material powders were weighed and mixed so that the total content was 100 mol%, with the ZnO content being 56.00 mol%, the ZnO content being 5.50 mol%, and the MnO content being 38.50 mol%. 0.5 parts by mass of polyvinyl alcohol was added to 100 parts by mass of the total mass of the mixture, and the mixture was sprayed with a spray dryer to obtain granules. The granules were then calcined in an air atmosphere at 750°C for 1 hour to obtain a calcined product. Next, sintered SiO was added as an auxiliary component to 100% by mass of the main component. 2 The content of SiO was 0.045% by mass. 2 was added to the calcined product, and similarly, Ca(OH) was added so that the CaO content after sintering was 0.025 mass%. 2 After sintering, 2 O 3 The content is 0.300 mass% Co. 3 O 4 After sintering, ZrO 2 The content of ZrO is 0.050 mass%. 2 was added.

[0044] Next, in the crushing process, the mixture of the calcined product and additives was crushed in a crusher so that the particle size after crushing had a D90 of 1.2 μm or less, to obtain crushed powder. Next, in the drying and granulation process, 1 part by mass of polyvinyl alcohol was added to this crushed powder per 100 parts by mass of the total mass of the crushed powder, and the mixture was sprayed with a spray dryer to obtain granules. Next, in the molding and sintering processes, the granules were molded into a toroidal core with an outer diameter of 12 mm, an inner diameter of 8 mm, and a height of 5 mm, and the oxygen partial pressure (PO 2 ) 3.3%, and sintered at a sintering temperature of 1150°C to obtain a sintered body (MnZn ferrite).

[0045] [Examples 2 to 11, Comparative Examples 1 to 12] The MnZn-based ferrites of Examples 2 to 11 and Comparative Examples 1 to 12 were obtained in the same manner as in Example 1, except that in Example 1, the raw materials were mixed and added so that the content ratios of the main components and the subcomponents after sintering were as shown in Table 1.

[0046] <Evaluation> The maximum magnetic flux density Bm of MnZn ferrite at 100°C was measured by winding a copper wire 22 times on the primary side and 22 times on the secondary side of a molded toroidal core to prepare a sample, and using a BH analyzer. The magnetic permeability μ of MnZn ferrite at 25°C was measured by winding a copper wire 5 times on a molded toroidal core to prepare a sample, and using an impedance analyzer. The unit volume core loss (Pcv) of MnZn ferrite at 100°C, 1MHz, and 50mT was measured by winding a copper wire 5 times on the primary side and 5 times on the secondary side of a molded toroidal core to prepare a sample, and using a BH analyzer. The sintered density was measured by the Archimedes method. The crushed particle size D90 was obtained by measuring the slurry of the crushed powder obtained in the manufacturing process of the above examples and comparative examples with a wet particle size distribution measuring device. The average grain size was calculated by image analysis of the images obtained by mirror-polishing each of the MnZn ferrites obtained in the examples and comparative examples, dissolving the grain boundary phase by etching, and observing the images with a microscope. The measurements were performed on 100 grains each. The results are shown in Table 1.

[0047] [Table 1]

[0048] [Summary of results] In 100mol% of main components, Fe 2 O 3 The content is 56.00 to 59.00 mol%, ZnO is 2.50 to 7.00 mol%, and the balance is MnO. The auxiliary component is SiO 2 0.010 to 0.050 mass%, CaO 0.020 to 0.060 mass%, Co 2 O 3 0.150 to 0.350 mass%, ZrO 2 In the MnZn-based ferrites of Examples 1 to 11 containing 0.000 to 0.100 mass %, the maximum magnetic flux density Bm at 100° C. is 450 mT or more, and the unit volume core loss (Pcv) at 100° C., 1 MHz, and 50 mT is 250 mW / cm 3 The magnetic permeability μ at 25°C is 450 or more, and the sintered density is 4.9 g / cm 3That's all.

[0049] While the present invention has been described above in accordance with the above-described embodiment, the present invention is not limited to the configuration of the above-described embodiment, and naturally includes various modifications, alterations, and combinations that may be made by a person skilled in the art within the scope of the invention as defined in the claims of the present application.

Claims

1. Fe 2 O 3 and ZnO and MnO as main components, In 100 mol% of the main components, Fe 2 O 3 is 56.0 to 59.0 mol %, ZnO is 2.5 to 7.0 mol %, and the remainder is MnO; As a subcomponent, SiO 2 0.010 to 0.050 mass%, CaO 0.020 to 0.060 mass%, Co 2 O 3 Contains 0.150 to 0.350 mass% MnZn ferrite.

2. The MnZn-based ferrite according to claim 1, further comprising 0.010 to 0.100 mass % of ZrO as an accessory component.

3. 3. The MnZn ferrite according to claim 1, having a maximum magnetic flux density Bm of 450 mT or more at 100°C.

4. Sintered density is 4.9 g / cm 3 The MnZn-based ferrite according to claim 1 or 2.

5. Core loss per unit volume (Pcv) at 100°C, 1MHz, and 50mT is 250mW / cm 3 The MnZn-based ferrite according to claim 1 or 2, wherein:

6. 3. The MnZn-based ferrite according to claim 1, having a magnetic permeability μ of 450 or more at 25° C.

7. A method for producing MnZn-based ferrite according to any one of claims 1 to 6, After sintering, Fe in 100 mol% of the main component 2 O 3 mixing raw materials containing each main component so that the content of each main component is 56.0 to 59.0 mol %, ZnO is 2.5 to 7.0 mol %, and the remainder is MnO; After sintering, SiO 2 0.010 to 0.050 mass%, CaO 0.020 to 0.060 mass%, Co 2 O 3 adding a raw material containing each of the subcomponents so that the content is 0.150 to 0.350 mass %; The resulting mixed powder is pulverized until it becomes a pulverized powder having a D90 particle size of 1.2 μm or less. A method for producing MnZn-based ferrite.

8. The method for producing MnZn ferrite according to claim 7, further comprising a step of molding the crushed powder and heat treating the molded powder at 1150 to 1250°C.

Citation Information

Patent Citations

  • LOW-LOSS Mn-Zn FERRITE AND UTILIZING THE SAME, ELECTRONIC PART AND SWITCHING POWER SUPPLY

    WO2006054749A1

  • MnZn-BASED FERRITE SINTERED BODY

    WO2018181242A1